Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Pasien Kanker Yang Menjalani Kemoterapi Di RS Kanker Dharmais Tahun 2022 - Lidia Rosaria; Yuni Susilowati; Zahrah Maulidia Septimar (Pusat Riset dan Inovasi Nasional, 2024)
Introduction: The World Health Organization (WHO) reports that cancer sufferers worldwide in 2020 will reach 19.3 million cases with a death rate of up to 10 million people. Riskesdas data for 2018 shows the prevalence of cancer in Indonesia is 1.49%. Chemotherapy in cancer patients often causes anxiety as a psychological effect. Family is the closest person for cancer patients in dealing with their illness. Family support for cancer patients is needed to lift the patient's mentality and enthusiasm for life. Purpose: This study was to determine the relationship between family support and anxiety levels in cancer patients undergoing chemotherapy. Method: Correlational descriptive with cross sectional approach. The study was conducted at the Dharmais Cancer Hospital in December 2022 - January 2023, with a sample of 185 respondents taken using a purposive sampling technique. Results: 38.9% of cancer patients undergoing chemotherapy at Dharmais Cancer Hospital experienced severe anxiety, 49.7% patients experienced moderate anxiety, 11.4% of patients experienced mild anxiety, and most of the cancer patients had good family support (60.5%). The results of the bivariate analysis of the Spearman rank test obtained p value: 0.000, and r: 0.506. Conclusion: there is a significant relationship between family support and the anxiety level of cancer patients undergoing chemotherapy, where the better the family support, the lighter the anxiety of cancer patients undergoing chemotherapy